Pierwiastek onomastyczny w polskiej terminologii sportowej - Nowowiejski, Bogusław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
Polish sports vocabulary uses a variety of sources, including lexical elements of various origin that include foreign lexical elements. A fairly significant part of this vocabulary consists of words and expressions that include in their composition onomastic, toponymic and anthroponymic components. An analysis of this vocabulary proves that, from among sports terms with the onomastic component, nominations that stem from the Mediterranean, Scandinavian and Anglo-Saxon traditions are decidedly dominant, whereas those of Polish origin are rare and infrequent.